PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT MITRA ANDALAN LOGISTIK BANJARMASIN - Mailiana Mailiana; Diana Hayati (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of service quality partially on customer satisfaction at PT Mitra Andalan Logistik Banjarmasin. To determine the effect of service quality simultaneously on customer satisfaction at PT Mitra Andalan Logistik Banjarmasin. The research population is all consumers of PT Mitra Andalan Logistik Banjarmasin in 2020. The total population in this study is 253 people, as many as 86 consumers of PT Mitra Andalan Logistik Banjarmasin which will be used as the research sample size. The research method used in this study is a quantitative method with a survey approach. The results showed that there was an effect of tangible, reliability, responsiveness, assurance and empathy on customer satisfaction at PT Mitra Andalan Logistik Banjarmasin. This study succeeded in proving the sixth hypothesis which states that “there is a significant effect of service quality (tangible, reliability, responsiveness, assurance and empathy) on customer satisfaction at PT Mitra Andalan Logistik Banjarmasin.